Effect of Work Environment and Work Discipline On Employee Performance PT Sarana Sumut Ventura Ciputat South Tangerang City - Husain, Bachtiar Arifudin; Novendri, Indra; Sunarsi, Denok (PINISI Discretion Review, 2022)
This study aims to determine the effect of work environment and work discipline on employee performance, either partially or simultaneously at PT Sarana Sumut Ventura Ciputat employees, South Tangerang City. The analytical methods used in this research are validity test, reliability test, classical assumption test, descriptive analysis, simple linear regression test, multiple linear regression test, correlation coefficient test, coefficient of determination test, t test and f test. The population in this study were employees of PT Sarana Sumut Ventura Ciputat, South Tangerang City. With a total sampling of 65 respondents. The results of this study based on the coefficient of determination showed that the work environment and work discipline had a contribution to employee performance of 67% while the remaining 33% were other variables not examined. The results showed that the multiple linear regression equation was 0.277 + 0.473(X1) + 0.63 (X2), meaning that the employee's performance even without being influenced by the work environment and work discipline had an effect of 0.277. The value of the correlation coefficient of the work environment on employee performance is 0.816, meaning that the two variables have a strong level of relationship, the value of the correlation coefficient of work discipline on employee performance is 0.622, meaning that both variables have a strong levels of relationship. The results of testing the simultaneous effect of independent variables on the dependent variable obtained the value of F-count = 63.019 > F-table value = 3.15, so Hₒ is rejected and Hₐ is accepted. So it can be concluded that there is a significant influence between the work environment and work discipline on the performance of employees of PT Sarana Sumut Ventura Ciputat, South Tangerang City.